Pengaruh Harga Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Alat Kesehatan Pada Pt Kembar Medika Safety Kota Tangerang - Reza Fauzi; Triyadi Triyadi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The purpose of this study is to determine whether Price and Quality of Service simultaneously influence the Purchase Decision of Medical Devices at PT Kembar Medika Safety Tangerang City. The research method uses a quantitative method with a sample of 100 respondents. The data feasibility test uses a validity test, a reliability test and a classical assumption test. Technical data analysis uses a simple linear regression test, multiple linear regression test, determination test and hypothesis test. The results of this study are Price has a positive and significant effect on Purchase Decisions, this is proven by the results of the partial test showing a t-count value of 7.207> t-table 1.660 with a significance level of 0.000 <0.05. Service Quality also influences Purchase Decisions, this is proven by the results of the partial test showing a tcount value of 7.996> ttable 1.660 with a significance value of 0.000 <0.05. Then Price and Service Quality have a positive and significant effect on Purchasing Decisions, this is proven by the Fcount value of 43.015> Ftable 3.09 with a significance level of 0.000 <0.05. Based on the determination test, Price and Service Quality contribute to Purchasing Decisions by 47% and the remaining 53% is influenced by other variables not examined by researchers in this study.